2010
DOI: 10.1186/1744-9081-6-35
|View full text |Cite
|
Sign up to set email alerts
|

A novel, rapidly acquired and persistent spatial memory task that induces immediate early gene expression

Abstract: BackgroundThe Morris water maze task is a hippocampus-dependent learning and memory test that typically takes between 3 days to 2 weeks of training. This task is used to assess spatial learning and induces the expression of genes known to be crucial to learning and memory in the hippocampus. A major caveat in the protocol is the prolonged duration of training, and difficulty of assessing the time during training in which animals have learned the task. We introduce here a condensed version of the task that like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 33 publications
3
20
0
Order By: Relevance
“…Our observations are consistent with prior reports of CPPinduced cognitive impairments (Larkin et al 2008;Niimi et al 2008;Feldman et al 2010;Velazquez-Zamora et al 2011) and LTP disruption in the hippocampus and prefrontal cortex (Brun et al 2001). Additionally, Davies et al (2013a) demonstrated that GluN2B receptors in medial prefrontal cortex were critical to OST performance.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our observations are consistent with prior reports of CPPinduced cognitive impairments (Larkin et al 2008;Niimi et al 2008;Feldman et al 2010;Velazquez-Zamora et al 2011) and LTP disruption in the hippocampus and prefrontal cortex (Brun et al 2001). Additionally, Davies et al (2013a) demonstrated that GluN2B receptors in medial prefrontal cortex were critical to OST performance.…”
Section: Discussionsupporting
confidence: 92%
“…The competitive NMDA-r antagonist 3-(2-carboxypiperazin-4-yl)propyl-1-phosphonic acid (CPP), which has previously been shown to impair memory (Larkin et al 2008;Niimi et al 2008;Feldman et al 2010;Velazquez-Zamora et al 2011) and to block long-term potentiation (Brun et al 2001), has also been shown to impair span in a study using a variable trial adaptation of the OST. Davies et al (2013a) demonstrated that systemic administration of CPP or the GluN2B-selective antagonist Ro 25-6981 impaired span without affecting nonspecific performance measures, indicating that competitive NMDA-r antagonists produce effects selective to the OST, as well.…”
mentioning
confidence: 99%
“…Other protocols have involved much longer inter-trial intervals (8-75 min) to reportedly assess working memory in rats (Hoane et al, 2008; Sarihi et al, 2000). Some more recent protocols have suggested that shorter inter-trial intervals (10-15 sec) should be used to accurately assess working memory (Aultman and Moghaddam, 2001; Feldman et al, 2010; Vorhees and Williams, 2006). Shorter inter-trial intervals (10-20 sec) may provide more meaningful comparisons with the radial arm maze and with human data (Cowan, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Encoding long-term memories requires more research into the range of times that can be used for spacing, the number of instructional repetitions, and identifying other protocols that induce LTP and LTM encoding. For example, LTP can be triggered in rats in very short spaces by alternating hidden and visual cues (Feldman et al, 2010), using 10 min spaces without stimuli (Morris, 2003; Fields, 2005), and spaces of an hour or more (Kramár et al, 2012). Evidence from other species (Jin et al, 2011) and recent LTP research cast further light on these issues (Redondo and Morris, 2011).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%